Aeromonas primary wound infection of a diver in polluted waters. - Joseph, S W (1979)
Two separate species of Aeromonas, A. sobria (not listed as a species in Bergey's Manual of Determinative Bacteriology, 8th ed.) and A. hydrophila, were primary pathogens isolated from the leg wound of a diver conducting operations in polluted waters. This is the first recorded instance of a primary infection of soft tissue in a human caused by two species of Aeromonas, one of which was resistant to tetracycline. Because of the very rapid development of this wound infection, cytotoxicity of these organisms was examined in several biological systems. A. sobria was hemolytic for sheep erythrocytes, cytotoxic for Y-1 adrenal cells, and enterotoxic in rabbit ligated intestinal loops, whereas A. hydrophila was hemolytic and cytotoxic. Pertinent clinical, bacteriological, and environmental features of the case are presented.